Management of monochorinic twin pregnancies in west of Scotland. (18th April 2012) - Wu, P; Moss, H; MacKenzie, F; Osman, I; Ledingham, MA; Santangeli, L; Oswald, N; Gibson, JL
Abstract : During 2010, an audit of monochorionic twin management was undertaken in Glasgow and Clyde hospitals with 15, 000 annual deliveries. Practice was compared against RCOG guideline.1 Thirty-seven MCDA and three MCMA cases were identified. All women had ultrasound examination for chorionicity, which was performed ≤13 weeks in 36 women (90%). Twenty-three patients (58%) had recorded photographic confirmation of this. Thirty cases (75%) were offered NT assessment, of which 14 declined. Of the 7 patients not offered, 2 were too late in gestation whilst 1 requested amniocentesis. All cohorts had detailed ultrasound scan. Only 1 case did not have extended cardiac views. Thirty-two women (80%) had ultrasound examinations from 16 weeks and 36 patients (90%) had scans every 2-3 weeks. Three women had single fetal death, of which 2 had selective reduction. Following this, all were assessed in a tertiary centre and had fetal MRI performed. Six cases of TTTS were identified. All were diagnosed ≤24 weeks. Two patients had stage 3 TTTS and were treated with laser ablation. One patient booked at 19 weeks with TTTS and IUDs, otherwise all resulted in live births. Overall, 32 MCDA pregnancies (86%) had at least one live birth, 23 (72%) delivered before 37 weeks, with 21 of these (91%) having received steroids. The remainder delivered between 37-38 weeks. Three MCMA pregnancies were delivered by Caesarean section at 32 weeks after steroid administration, and all had live births. We conclude that most RCOG recommendations have been implemented into practice, with some scope for improvement.